2015
DOI: 10.1002/imhj.21499
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Attachment in Abused and Neglected Mothers: The Role of Trauma-Specific Reflective Functioning

Abstract: There are still important gaps in our knowledge regarding the intergenerational transmission of attachment from mother to child, especially in mothers with childhood histories of abuse and neglect (CA&N). This study examined the contributions of reflective function concerning general attachment relationships, and specifically concerning trauma, as well as those of maternal attachment states of mind to the prediction of infant attachment disorganization in a sample of mothers with CA&N and their infants, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
177
1
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(202 citation statements)
references
References 55 publications
9
177
1
15
Order By: Relevance
“…Further support came from a recent study (Berthelot et al, 2015) that found that children of abused and neglected mothers were classified as insecure in 83% of cases and disorganized in almost half of the cases, with high concordance between maternal and child attachment. Furthermore, they found that maternal unresolved state of mind regarding the trauma and low reflective functioning about the trauma independently contributed to infant disorganization of attachment.…”
Section: Resultsmentioning
confidence: 96%
“…Further support came from a recent study (Berthelot et al, 2015) that found that children of abused and neglected mothers were classified as insecure in 83% of cases and disorganized in almost half of the cases, with high concordance between maternal and child attachment. Furthermore, they found that maternal unresolved state of mind regarding the trauma and low reflective functioning about the trauma independently contributed to infant disorganization of attachment.…”
Section: Resultsmentioning
confidence: 96%
“…This delineates the pioneering work by Fraiberg et al (1975) that spoke to the “presence” of past traumatic experiences in the relational dynamics between caregiver and child. Finally, it is important to note that the experience of trauma alone does not necessarily lead to insecure attachment styles, however the experience of trauma that is not resolved or worked through has shown to lead to increased insecurity of attachment in children of parents who have experienced trauma early on (Berthelot et al, 2015). …”
Section: Early Experiences Of Trauma and The Attachment Systemmentioning
confidence: 99%
“…Attachment theory suggests that the parent–child bond is biologically based and essential for survival of the child—this bond develops into an attachment style that is shaped in early childhood and is apparent throughout the life course 30. Insecure attachment between parent and child as symptomatised by parentification, rejection, fear and unresolved trauma has been found to be highly prevalent (83%) in children whose parents were subjected to childhood trauma 31 32. Maternal experience of childhood trauma, mediated by maternal mental health, has been shown to be a significant predictor of child health and mental health outcomes, and maternal experience of high betrayal trauma, in addition to the level of perceived intervention by her own parents, was shown to be the only significant predictor of her own parent attachment style with her infant child 33 34.…”
Section: Introductionmentioning
confidence: 99%